Love after the tale of genji : rewriting the world of the shining prince - D'Etcheverry, Charo B. (Harvard East Asian monographs ;, 2007)
"The eleventh-century masterpiece The Tale of Genji casts a long shadow across the literary terrain of the Heian period (794-1185)." "Charo B. D'Etcheverry calls for a reevaluation of late Heian fiction by shedding new light upon this undervalued body of work. D'Etcheverry examines three representative texts - The Tale of Sagoromo, The Tale of the Hamamatsu Middle Counselor, and Nezame at Night - as legitimate heirs to the literary legacy of Genji and as valuable indexes to the literary tastes and readerly expectations that evolved over the Heian period." "Balancing careful analyses of plot, character, and motif with keen insights into the cultural and political milieu of the late Heian period, D'Etcheverry argues that we should read such works not as mere derivatives of a canonical text, but as dynamic fictional commentaries and variations upon the tropes and subplots that continue to resonate with readers of Genji."--Jacket